Sinergi Peran Majelis Rakyat Papua untuk Akselerasi Pertumbuhan Ekonomi Daerah Papua - Cabui, Cornelia Evelin (Indo-MathEdu Intellectuals Journal, 2025)
Tourism development in the Land of Papua holds strategic potential in driving regional economic growth and improving community welfare, particularly for the Indigenous Papuans (OAP). Data collection techniques were conducted through library research, which involves reviewing relevant literature as a theoretical and contextual basis. The sources of this research data are scientific articles published in various scientific journals and indexed in Google Scholar. Data analysis was carried out qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The analysis results indicate that to ensure inclusive and sustainable development, active involvement of the Papua People's Assembly (MRP) and indigenous communities is required at every stage of tourism investment planning and implementation. An approach based on local uniqueness and the utilization of Geographic Information System (GIS) technology in mapping regional potential and SMEs is key to formulating effective development strategies. Moreover, tourism development policies need to be designed collaboratively with a socio-legal approach that recognizes customary law and the social structures of Papuan society. Cross-agency coordination and the provision of fiscal incentives to investors committed to empowering local communities are expected to create a fair investment climate. Strengthening indicators of local economic impact and implementing the principle of Free, Prior and Informed Consent (FPIC) in tourism projects are important steps in maintaining social and cultural sustainability